2014
DOI: 10.1016/j.ijid.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Optimal tigecycline dosage regimen is urgently needed: results from a pharmacokinetic/pharmacodynamic analysis of tigecycline by Monte Carlo simulation

Abstract: In the absence of new drugs on the horizon, rather than using a single fixed dosing regimen, tigecycline dosing needs to be optimized in order to achieve the desired successful clinical response and to prevent an escalation in drug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…However, studies conducted over 24 h were unable to ascertain whether the suppression of resistant bacterial subpopulations is sustained beyond 24 h at the studied concentrations. In an attempt to optimise tigecycline regimens, Xie et al concluded that the clinical effectiveness of current standard tigecycline dosing was less than adequate given the continued resistance and reduced AUC in vivo against MDR A. baumannii strains with enhanced MICs [15]. Therefore, bacterial density and duration of in vitro studies are important to consider when evaluating these polymyxin combinations.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies conducted over 24 h were unable to ascertain whether the suppression of resistant bacterial subpopulations is sustained beyond 24 h at the studied concentrations. In an attempt to optimise tigecycline regimens, Xie et al concluded that the clinical effectiveness of current standard tigecycline dosing was less than adequate given the continued resistance and reduced AUC in vivo against MDR A. baumannii strains with enhanced MICs [15]. Therefore, bacterial density and duration of in vitro studies are important to consider when evaluating these polymyxin combinations.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, current tigecycline dosing strategies (especially monotherapy) may not be optimal for treating multidrug-resistant bacteria such as CRKP. 29 Lastly, tigecycline was also shown in murine models to promote the intestinal overgrowth of CRKP. 22 In subgroup analysis, the association between tigecycline treatment and CRKP readmission was observed in both the group of patients with CRKP infection as well as the group with CRKP colonization.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, the optimum therapeutic choices can also be based on the pharmacokinetic/pharmacodynamic model or Monte-Carlo simulation to obtain the most effective treatment. 18 This study has some limitations. The long-term monitoring period is still warranted to comprehensively investigate crossresistance or relation between other classes of antimicrobial agents and the resistance in AB.…”
Section: Discussionmentioning
confidence: 91%